What causes the large extensions of red supergiant atmospheres?: comparisons of interferometric observations with 1D hydrostatic, 3D convection, and 1D pulsating model atmospheres - Arroyo-Torres, Belén; Wittkowski, Markus; Chiavassa, A.; Scholz, Michael; Freytag, Bernd; Marcaide, J. M.; Hauschildt, Peter H.; Wood, P. R.; Abellan, F. J. (Astronomy and astrophysics, 2015)
Aims. This research has two main goals. First, we present the atmospheric structure and the fundamental parameters of three red supergiants (RSGs), increasing the sample of RSGs observed by near-infrared spectro-interferometry. Additionally, we test possible mechanisms that may explain the large observed atmospheric extensions of RSGs.Methods. We carried out spectro-interferometric observations of the RSGs V602 Car, HD 95687, and HD 183589 in the near-infrared K-band (1.92−2.47 μm) with the VLTI/AMBER instrument at medium spectral resolution (R ~ 1500). To categorize and comprehend the extended atmospheres, we compared our observational results to predictions by available hydrostatic PHOENIX, available 3D convection, and new 1D self-excited pulsation models of RSGs.Results. Our near-infrared flux spectra of V602 Car, HD 95687, and HD 183589 are well reproduced by the PHOENIX model atmospheres. The continuum visibility values are consistent with a limb-darkened disk as predicted by the PHOENIX models, allowing us to determine the angular diameter and the fundamental parameters of our sources. Nonetheless, in the case of V602 Car and HD 95686, the PHOENIX model visibilities do not predict the large observed extensions of molecular layers, most remarkably in the CO bands. Likewise, the 3D convection models and the 1D pulsation models with typical parameters of RSGs lead to compact atmospheric structures as well, which are similar to the structure of the hydrostatic PHOENIX models. They can also not explain the observed decreases in the visibilities and thus the large atmospheric molecular extensions. The full sample of our RSGs indicates increasing observed atmospheric extensions with increasing luminosity and decreasing surface gravity, and no correlation with effective temperature or variability amplitude.Conclusions. The location of our RSG sources in the Hertzsprung-Russell diagram is confirmed to be consistent with the red limits of recent evolutionary tracks. The observed extensions of the atmospheric layers of our sample of RSGs are comparable to those of Mira stars. This phenomenon is not predicted by any of the considered model atmospheres including available 3D convection and new 1D pulsation models of RSGs. This confirms that neither convection nor pulsation alone can levitate the molecular atmospheres of RSGs. Our observed correlation of atmospheric extension with luminosity supports a scenario of radiative acceleration on Doppler-shifted molecular lines.
Gesehen am 28.07.2020